2022
DOI: 10.1021/acs.jmedchem.2c00974
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Kinetic Relationship Studies for the Development of Long Residence Time LpxC Inhibitors

Abstract: UDP-3-O-(R-3-hydroxymyristoyl)-N-acetylglucosamine deacetylase (LpxC) is a promising drug target in Gram-negative bacteria. Previously, we described a correlation between the residence time of inhibitors on Pseudomonas aeruginosa LpxC (paLpxC) and the post-antibiotic effect (PAE) caused by the inhibitors on the growth of P. aeruginosa. Given that drugs with prolonged activity following compound removal may have advantages in dosing regimens, we have explored the structure–kinetic relationship for paLpxC inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The dissociation rate of mesotrione from the Avena sativa HPPD (5.75 × 10 –6 s –1 ) was faster than that from the Arabidopsis thaliana (7.50 × 10 –4 s –1 ), suggesting that the dynamic behavior of H11 affected the dissociation rate of the inhibitor . Such difference in the dissociation rate of inhibitors might be due to the conformational change of protein, as reported in previous studies on several inhibitors, such as UDP-3- O -acyl- N -acetylglucosamine deacetylase, enoyl acyl carrier protein reductase, and human immunodeficiency virus type 1 (HIV-1) protease inhibitors. Notably, a previous study reported that even a single residue mutation in HIV-1 protease alters the dynamic behavior of the flap and increases the dissociation rate of the inhibitor . Therefore, we suggest that the difference in the dynamic behavior of H11 between plants affected the dissociation rate of the inhibitor.…”
Section: Resultsmentioning
confidence: 65%
“…The dissociation rate of mesotrione from the Avena sativa HPPD (5.75 × 10 –6 s –1 ) was faster than that from the Arabidopsis thaliana (7.50 × 10 –4 s –1 ), suggesting that the dynamic behavior of H11 affected the dissociation rate of the inhibitor . Such difference in the dissociation rate of inhibitors might be due to the conformational change of protein, as reported in previous studies on several inhibitors, such as UDP-3- O -acyl- N -acetylglucosamine deacetylase, enoyl acyl carrier protein reductase, and human immunodeficiency virus type 1 (HIV-1) protease inhibitors. Notably, a previous study reported that even a single residue mutation in HIV-1 protease alters the dynamic behavior of the flap and increases the dissociation rate of the inhibitor . Therefore, we suggest that the difference in the dynamic behavior of H11 between plants affected the dissociation rate of the inhibitor.…”
Section: Resultsmentioning
confidence: 65%
“…Possibly, with the current rate of methodological improvements, our research community may reach this threshold in a few years. In the end, it might be that the insights the community gains from its research will be put to best use in the parametrization of structure–kinetics relationships , or machine-learning models ,, that will provide a sufficiently fast estimate of unbinding and binding kinetics for computer-aided drug design.…”
Section: Discussionmentioning
confidence: 99%
“…LpxC is a zinc metalloenzyme that plays an important role in the biosynthesis of lipid A, a glucosamine disaccharide that anchors lipopolysaccharide (LPS) to the outer membrane of Gram-negative bacteria. 71,72 Le et al working at Novartis identified by virtual screening an oxazolidine derivative with potent LpxC inhibitory activity ( K d = 0.065 nM). 73 Compound 45 (Fig.…”
Section: Oxazolidinones As Antibacterial Agentsmentioning
confidence: 99%